Increasing Awareness and Talk Time through Free Messaging Apps - Pollard, Andrew (2015)
For many people, mobile phones are a part of modern life. Although the purpose of this technology revolves around language and communication, its application to language learning still appears to be underutilized. This is changing, as the widespread use of this handheld technology offers numerous opportunities to use functions that are ideal for exposing learners to communicative interaction on their language-learning journey.